Dysadherin expression promotes the motility and survival of human breast cancer cells by AKT activation - Lee, Yoo‐Kyung (Cancer Sci, 2012)
High dysadherin expression has been recognized as a biological predictor of metastasis and poor prognosis for many different cancer types; however, the molecular mechanisms of how dysadherin affects cancer progression are still poorly understood. In this study, we examined whether AKT signaling could link dysadherin expression with downstream events that promote the metastatic potential of human breast cancer cells. Immunohistochemical analysis of breast cancer tissues showed that dysadherin expression was highly associated with elevated expression of phospho‐AKT. The introduction of dysadherin cDNA into BT‐474, MCF‐7 and T‐47D breast cancer cell lines enhanced their levels of AKT phosphorylation, while knockdown of dysadherin in MDA‐MB‐231 and Hs578T breast cancer cell lines suppressed AKT phosphorylation. Treatment with the AKT inhibitor triciribine suppressed dysadherin‐mediated pro‐metastatic effects, including epithelial–mesenchymal transition, cell motility and drug resistance. These findings suggest that dysadherin might contribute to breast cancer progression through AKT activation. (Cancer Sci 2012; 103: 1280–1289)